The Influence of Product Quality, Servicescape, Brand Image on Customer Satisfaction at Seirock-Ya Ramen Mall Kelapa Gading - Wanda Aliza; Jamaludin Khalid MM (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to investigate how customer satisfaction at SeiRock-Ya Ramen Mall Kelapa Gading is influenced by product quality, servicescape, and brand image. Questionnaires sent to 100 people were used to collect data. Quantitative descriptive analysis method used in this study. The investigation is carried out using the non-probability inspection method. Variable X1 product quality has a partial effect on customer satisfaction at Seirock-ya Ramen Mall Kelapa Gading; variable X2, servicescape, has a partial effect on customer satisfaction at Seirock-ya Ramen; and the findings of variable X3, namely brand image has a partial effect on customer satisfaction at Seirock-ya Ramen Mall Kelapa Gading. so that customer satisfaction is influenced simultaneously by Product Quality, Servicescape, and Brand Image. Companies must be able to maximize the service, quality and facilities of SeiRock-Ya Ramen in order to increase sales and customer satisfaction because the role of each variable is related to customer satisfaction.